New records of bats (Chiroptera) from Santa Cruz province (Argentina) and the southernmost record of Lasiurus varius (Poeppig, 1835) for Argentina - Díaz, María Mónica (2017)
Here, we report new records for the distribution in Argentina of 3 bat species from the family Vespertilionidae: Lasiurus varius (Poeppig, 1835), Histiotus magellanicus (Philippi, 1866), and Myotis chiloensis (Waterhouse, 1838). The range of L. varius is extended by more than 800 km south of the previous known limit, representing the southernmost known occurrence for the species in Argentina. The new information for M. chiloensis fills a previous existing gap between records known from Chubut and Tierra del Fuego. Similarly, the new record of H. magellanicus also completes its known distribution in the Santa Cruz province.